1995
DOI: 10.1080/00480169.1995.35898
|View full text |Cite
|
Sign up to set email alerts
|

The prophylactic effect of a dry-cow antibiotic againstStreptococcus uberis

Abstract: The prophylactic use of a dry-cow antibiotic for reducing the incidence of mastitis due to Streptococcus uberis was studied in four seasonally calving dairy herds involving 378 cows. The treatment was a long-acting dry-cow antibiotic preparation administered immediately after the last milking of lactation. New intramammary infections were identified by comparing the bacteriological status of quarters at drying off with that after calving, or through manual udder palpation during the dry period. The administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
2
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 6 publications
3
95
2
4
Order By: Relevance
“…In a meta-analysis of 5 studies, blanket DCT was compared with selective DCT and showed no significant difference in protection against new IMI in 3 studies when cow-level selection was practiced for drying off with antibiotics. This indicates no preventive effect of DCT in this approach (Rindsig et al, 1978;Browning et al, 1994;Williamson et al, 1995). However, these studies are hard to compare with our study because they were carried out over 20 yr ago in herds with different housing systems and with different production levels.…”
Section: Discussionmentioning
confidence: 42%
“…In a meta-analysis of 5 studies, blanket DCT was compared with selective DCT and showed no significant difference in protection against new IMI in 3 studies when cow-level selection was practiced for drying off with antibiotics. This indicates no preventive effect of DCT in this approach (Rindsig et al, 1978;Browning et al, 1994;Williamson et al, 1995). However, these studies are hard to compare with our study because they were carried out over 20 yr ago in herds with different housing systems and with different production levels.…”
Section: Discussionmentioning
confidence: 42%
“…However, most other studies described lower rates of between 4 % and 14 % 4,30,36,47,52,58 . The expected rate of new IMIs during the dry period in bacteria-negative quarters that were untreated was reported by Eberhart 14 to vary between 8 % and 12 % while Berry 4 reported new infection rates of 34.4 % in untreated cows compared with 10.3 % in treated cows.…”
Section: New Imismentioning
confidence: 89%
“…A large variation in intramammary overall cure rate was reported by various authors 17,20,35,42,46,52,54,58 of between 21.2 % and 80 %. Rainard 43 estimated that between 70 % and 90 % of infections present at drying off can be eliminated with dry cow therapy and the cure rate of IMI during the dry period was found to vary significantly between major and minor pathogens 14,46 .…”
Section: Cure Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested that minor pathogens break down teat defenses or interfere with the keratin plug, allowing major pathogens to penetrate and initiate infection (Hogan et al, 1988;Williamson et al, 1995;Zadoks et al, 2001b;Berry and Hillerton, 2002a,b). It has also been shown that the presence of subclinical mastitis aids in the growth of major pathogens in the udder by the release of nutrients necessary for their survival (Mattila et al, 1984;Mattila and Sandholm, 1986;Kitt and Leigh, 1997).…”
Section: Meta-regressionsmentioning
confidence: 99%